Dérouter le lecteur ou comment dépasser le stéréotype du roman de la route au Québec au XXIe siècle – l’exemple de François Blais - Berek, Ewelina (Romanica Silesiana, 2021)
The article discusses the stereotype of road novel in Québec in the 21st century, exemplified by François Blais’s sixth novel entitled Document 1 published in 2012. Blais’s novel appears different from the typical road novels by playing with the genre’s codes in order to create something altogether new. The aim of the article is to shed light on the character development, the representations of place and the journey itself presented in the novel.